2014
DOI: 10.1155/2014/453607
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion Behaviour of Detonation Gun Sprayed Al2O3-40TiO2 Coating on Nickel Based Superalloys at 900°C

Abstract: Hot corrosion is the major degradation mechanism of failure of boiler and gas turbine components. These failures occur because of the usage of wide range of fuels such as, coal and oil at the elevated temperatures. Nickel based superalloys having excellent mechanical strength and creep resistance at elevated temperature are used under such environment but they lack resistance to hot corrosion at high temperature. To overcome these problems hot corrosion resistant coatings are deposited on these materials. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…22,31 The weight gain of the Al 2 O 3 -40% TiO 2 coating deposited by LVOF method on Superni 601 and Superco 605 superalloys in the present study is also compared with weight gain of Al 2 O 3 -40% TiO 2 coating deposited by the detonation gun method on Superni 718 and AE 435 superalloys during hot corrosion study at 900 • C in Na 2 SO 4 -82% Fe 2 (SO 4 ) 3 environment for 50 cycles. 15 The weight gain of Al 2 O 3 -40% TiO 2 coating deposited by the LVOF method in present study is found slightly higher than the weight gain of Al 2 O 3 −40% TiO 2 coating deposited by the detonation gun method. The weight gain during hot corrosion of the Al 2 O 3 -40% TiO 2 coating is found higher than the weight gains during oxidation of the same coating due to the presence of aggressive Na 2 SO 4 -82% Fe 2 (SO 4 ) 3 environment.…”
Section: Number Of Cyclescontrasting
confidence: 58%
See 1 more Smart Citation
“…22,31 The weight gain of the Al 2 O 3 -40% TiO 2 coating deposited by LVOF method on Superni 601 and Superco 605 superalloys in the present study is also compared with weight gain of Al 2 O 3 -40% TiO 2 coating deposited by the detonation gun method on Superni 718 and AE 435 superalloys during hot corrosion study at 900 • C in Na 2 SO 4 -82% Fe 2 (SO 4 ) 3 environment for 50 cycles. 15 The weight gain of Al 2 O 3 -40% TiO 2 coating deposited by the LVOF method in present study is found slightly higher than the weight gain of Al 2 O 3 −40% TiO 2 coating deposited by the detonation gun method. The weight gain during hot corrosion of the Al 2 O 3 -40% TiO 2 coating is found higher than the weight gains during oxidation of the same coating due to the presence of aggressive Na 2 SO 4 -82% Fe 2 (SO 4 ) 3 environment.…”
Section: Number Of Cyclescontrasting
confidence: 58%
“…The necessities for higher performance and increased efficiency have resulted in the progressive increase in their operation temperatures. [11][12][13][14][15] Ceramics are widely applied as protective coating because of their excellent wear, corrosion and high temperature oxidation resistance. [16][17][18] Surface coatings of aluminium and titanium oxides are used to improve the resistances of materials against wear, erosion, cavitations, fretting and corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Coating of cermets on the superalloys can certainly be beneficial in enhancing the life of operation of the components made of superalloys [9][10][11]. HVOF technique is the most popularly used thermal spray coating technique of deposition of cermets onto the substrates, as it is proved to provide a coating with properties like good bond strength between substrate and coating, less porosity, and laminar structured coating [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…6 Thermal spray coatings are widely used to improve the oxidation and wear resistance for such applications. [7][8][9] In the thermal spray industry, Al 2 O 3 alloy with TiO 2 ceramics is known for environmental compatibility. Al 2 O 3 -TiO 2 coatings are used as protective coatings against corrosive media.…”
Section: Introductionmentioning
confidence: 99%